Effects of feeding probiotic Lactobacillus spp. on growth performances, scours and Escherichia coli shedding in dairy calves (Bangladesh Journal of Livestock Research, 2020)
A feeding trial was conducted on 21 crossbred (Local×Friesian, Local×Sahiwal, Sahiwal×Friesian) calves of around one week age for a period of 70 days with the objective of evaluating effects of probiotic on growth performances of calves. Calves were selected and distributed equally into three groups maintaining equal sex ratio in each group, namely the farm practice (FP), control and probiotic groups. The calves were fed on milk as 12% of their live weight up to 14 days and then 10% milk of their live weight up to 70 days of age and wheat bran was supplied to the calves from 50th day at the rate of 250g/calf. The calves of probiotic group werefedaprobiotic mixture containing lactic acid bacteria (LAB) at 0.5 g /d. The data of feed intake and growth for all groups were recorded up to 35 days and then up to 70 days for probiotic and control groups. The calves under probiotic group were achieved 82.8% and 74.5% higher gain (P